Exploring the Effect of Science Teachers’ Age Group on Technological Knowledge, Technological Content and Pedagogical Knowledge in Augmented Reality - Nelson Cyril; Ng Khar Thoe; Deva Nanthini Sinniah; Murugan Rajoo; Sivaranjini Sinniah; Wan Noor Adzmin; Yoon Fah Lay; Sharfuddin Abdul Shukor (Universitas Muhammadiyah Purwokerto, 2022)
This study describes the effect of science teachers’ cognizance of technological knowledge, technological content and pedagogical knowledge towards augmented reality across five age groups. This pilot study involved 44 science teachers from Penang, Malaysia using a 5-point Likert scale instrument. The administered survey instruments consisted of 18 questions on technological knowledge; technological content knowledge; and technological pedagogical knowledge. The analyses showed that generally teachers had good technological knowledge but their technological content and pedagogical knowledge seemed to be less. The results also showed that two items had significant differences using the Kruskal Wallis non-parametric test. The findings would be used as a tool to revise the servicing teachers’ technological practices using augmented reality incorporated in their daily teaching and learning sessions to obtain better learning outcomes. The research findings could also be used for further research exploring other variables affecting teachers’ technological knowledge. The intervention may be used in teachers’ training curriculum and continuing professional development in terms of determining their level of technological content and pedagogical knowledge that would increase the interest of students in learning and exploring science using Augmented Reality.